Chest wall coverage by using flaps muscular or musculocutaneous - Irigaray, Alberto (Cirugía del Uruguay, 1994)
T he author presents the different options for coverage of the thoracic wa/1 which is different from breast reconstruction. He describes the different types of flaps, emphasizing the importance of muscular or musculo-cutaneous flaps beca use of their benefficial effects, as they increase local irrigation and make possible the coverage of uncovered organs such as ribs, cartilage and víscera.